حتمية التغييرات المحاسبية في القطاع العام في إطار التسيير العمومي الحديث: The inevitability of accounting changes in the public sector in the framework of modern public management - عمر آيت مختار; بلحمري سمية (Journal of North African Economies, 2025)
This topic acquires its importance from the strategic position of the public accounting system in the state’s financial management system, where the state’s accounting system produces financial reports that display the activity of public sector units that are used for the purposes of planning, control and evaluation of the performance of government units to control the management of public money. The new public management is a “coordinated program for public sector reform that aims to replace management with management, replace formal bureaucracy with markets or contracts to the maximum extent possible, and reduce the size of the public sector. This study aims mainly to highlight the relationship between public accounting and the new public management and linkage Between administrative reform and accounting reform in the public sector to implement economic reforms as a whole in order to try to reach that the new public management movement imposes a change in the foundations of public accounting adopted to measure performance.